2022
DOI: 10.21273/hortsci15984-21
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Garlic Quality and Yields to Various Types and Rates of Potassium Fertilizer Applications

Abstract: Potassium (K) is a critical plant nutrient that determines quality in a myriad of crops and increases production yields. However, excessive application of various types of K fertilizers can decrease both the food quality and yields, which translates as economic losses and food safety issues. The objectives of this study were to 1) elucidate the impacts of different application rates of various K fertilizers on garlic, with the aim to identify the optimal and most economical K fertilizer dosage and 2) compare t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The results showed that potassium could promote the development of underground bulbs and leaf growth, increase the plant height and stem diameter, increase the chlorophyll content, and make full use of light energy to enhance the photosynthetic efficiency, thus promoting the plant's growth and development. We also found that the bulb weight and bulb circumference decreased significantly with an excessive K fertilizer application, as also found in other crops [27,28], possibly because the application of an excessive amount of K hinders the absorption of other nutrients such as N and P, thereby negating the positive effects of K fertilization [29]. Potassium is involved in the synthesis, transportation, and transformation of sugars, where it can inhibit acid invertase and promote the activity of sucrose phosphate synthase to decrease the hydrolysis of sucrose and promote the accumulation of polysaccharides [30].…”
Section: Discussionsupporting
confidence: 86%
“…The results showed that potassium could promote the development of underground bulbs and leaf growth, increase the plant height and stem diameter, increase the chlorophyll content, and make full use of light energy to enhance the photosynthetic efficiency, thus promoting the plant's growth and development. We also found that the bulb weight and bulb circumference decreased significantly with an excessive K fertilizer application, as also found in other crops [27,28], possibly because the application of an excessive amount of K hinders the absorption of other nutrients such as N and P, thereby negating the positive effects of K fertilization [29]. Potassium is involved in the synthesis, transportation, and transformation of sugars, where it can inhibit acid invertase and promote the activity of sucrose phosphate synthase to decrease the hydrolysis of sucrose and promote the accumulation of polysaccharides [30].…”
Section: Discussionsupporting
confidence: 86%
“…Effect of special fertilizer on garlic bulb quality. adjusted the S:Cl ratio (3:1; Wang et al 2022). In addition, considering the long growth period of garlic ($210 d), 60% polyurethane controlled-release nitrogen fertilizer was used to instead of available nitrogen fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…On a global scale, the leading producers are China, India, Bangladesh, Korea, Egypt, and Spain. Garlic is predominantly grown in Asia (87%), where China and India collectively account for 78% of global production (Wang et al 2022). According to the Food and Agricultural Organization (FAO) database, the global production of garlic reached 30.7 million tons with a land area of 1.6 million hectares in 2019.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…After the leaves turned white, the absorbances (at 645 nm and 663 nm wavelengths) of the extracts were determined using an ultraviolet spectrophotometer. The leaf soluble sugar concentration was determined based on the anthrone colorimetry method (Wang et al 2022), with the modification that we incubated the sample solution for 10 min in a water bath at 95 C. The soluble protein concentration was determined according to the bicinchoninic acid method (Song et al 2015), with the modification that the sample solution was incubated for 30 min in water at 60 C.…”
Section: Methodsmentioning
confidence: 99%